The Effectiveness of Cognitive Behavioral Counseling using Cognitive Restructuring Techniques to Reduce Self-Injury Behavior among Vocational High School Students - Nur Dhian Mustang; Maudy Mursalin Madani (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Self-injury among adolescents is a growing mental health concern, particularly among vocational high school students facing academic, social, and personal pressures. Negative thinking patterns can lead students to adopt maladaptive coping strategies such as self-injury, highlighting the need for appropriate counseling interventions. Objective: This study aims to examine the effectiveness of cognitive restructuring techniques within the framework of Cognitive Behavioural Counseling in reducing self-injury behaviour among students at SMK Negeri 3 Makassar. Method: This research employed a quantitative, quasi-experimental design. The population consisted of 71 students, and the sample was selected purposively, yielding 10 students who reported self-injurious behaviour. The participants were divided into an experimental group and a control group. Data were collected through observation, interviews, documentation, and a self-injury behaviour scale. Data analysis was conducted using descriptive statistics and the Mann–Whitney test. Results: The experimental group showed a significant reduction in self-injury behaviour after cognitive restructuring techniques were implemented, compared to the control group. Conclusion: Cognitive restructuring techniques within Cognitive Behavioural Counseling are effective in reducing self-injury behaviour among vocational high school students. Contribution: This study contributes to the development of evidence-based counseling interventions and provides practical guidance for school counsellors in addressing self-injury behaviour among students in educational settings.